STUDI ETNOGRAFI TERFOKUS PADA PENYAKIT TUBERKULOSIS DI KABUPATEN KEBUMEN JAWA TENGAH - Suyatno - (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Baickgound: Tuberculosis is a complex problem, especially in the tleveloping countries. Among other problems, the most dfficult thing to handle is the difficulty in findtng the srffirer. The objective of this intcly is' to apply the ethnographic study to explore the case of tuberculosis in the community. Metiod: The'stucly oppiin, the cimmunity based design. The data was gathered with quantitative and qualitative methotl (in-clepth'inter-view) from the tuberculosis patient and the non-tuberculosis patient, some of key pet'son in the community, ancl health tuorker in 7 health center area in the district of Kebumen, Central Java. Results; The study showecl ihat 'TAC' was afamiliarterminologt of tuberculosis, and there were various local terminologies as tuberculosis symptoms. More patieits came to health care center with haemoptysis symptom. Conclusion; Almost all of them felt uncomfortable witi the durution and the side effect of antituberculosis medicine.Keywords: tuberculosis, ethnographic study, local terminology